Synthesis and Evaluation of the Antifungal and Toxicological Activity of Nitrofuran Derivatives - Vaso, Carolina Orlando [UNESP]; Pandolfi, Fabiana; Bila, Níura Madalena [UNESP]; De Vita, Daniela; Bortolami, Martina; Mendes-Giannini, Maria José Soares [UNESP]; Tudino, Valeria; Costi, Roberta; Costa-Orlandi, Caroline Barcelos [UNESP]; Fusco-Almeida, Ana Marisa [UNESP]; Scipione, Luigi (MDPI, 2022)
Fungal diseases affect more than 1 billion people worldwide. The constant global changes, the advent of new pandemics, and chronic diseases favor the diffusion of fungal pathogens such as Candida, Cryptococcus, Aspergillus, Trichophyton, Histoplasma capsulatum, and Paracoccidioides brasiliensis. In this work, a series of nitrofuran derivatives were synthesized and tested against different fungal species; most of them showed inhibitory activity, fungicide, and fungistatic profile. The minimal inhibitory concentration (MIC90) values for the most potent compounds range from 0.48 μg/mL against H. capsulatum (compound 11) and P. brasiliensis (compounds 3 and 9) to 0.98 μg/mL against Trichophyton rubrum and T. mentagrophytes (compounds 8, 9, 12, 13 and 8, 12, 13, respectively), and 3.9 μg/mL against Candida and Cryptococcus neoformans strains (compounds 1 and 5, respectively). In addition, all compounds showed low toxicity when tested in vitro on lung cell lines (A549 and MRC-5) and in vivo in Caenorhabditis elegans larvae. Many of them showed high selectivity index values. Thus, these studied nitrofuran derivatives proved to be potent against different fungal species, characterized by low toxicity and high selectivity; for these reasons, they may become promising compounds for the treatment of mycoses.
Keywords: Antifungal activity; Broad-spectrum antifungal; Caenorhabditis elegans larvae; Candida sp; Cryptococcus neoformans; Histoplasma capsulatum; Nitrofuran derivates; Paracoccidioides brasiliensis; Trichophyton mentagrophytes; Trichophyton rubrum